Balanced centricity and triads: strategies to reach ecosystem equilibrium in the arts sector - Quero-Gervilla, María José (My University, 2018)
The purpose of this paper is to analyze whether triads structure can facilitate or inhibit the evolution into a service ecosystem. The triad structure and the institutions that dominate the triads will determine the evolution into ecosystem, remain as triad or die. “Balanced centricity” in considered a desirable institution that increases the possibility for transforming triads into ecosystems through marketing equilibrium.
Keywords: Marketing - Congresos; Systems of value co-creation; Ecosystems; Value co-creation; Service Dominant Logic; Balanced centricity; Balance triad structure; Triads